Neuroprotective Proteins in Hypoxia-stressed Astrocyte-Derived Extracellular Vesicles - Bernal-Vicente, Berenice N.; Ponce, Isaac; Santos-Gutiérrez, Manuel; Ríos-Castro, Emmanuel; Tovar-y-Romo, Luis B. (Current Neuropharmacology, 2025)
BackgroundAdvances in mass spectrometry-based proteomic analysis have generated extensive protein data from cells involved in neurodegenerative diseases. The field of neuroproteomics is expanding to include the study of extracellular vesicles (EVs) to identify potential biomarkers for disease prevention and endogenous factors involved in neuroprotection.MethodsIn this study, rat cortical astrocytes in normoxia were cultured under normoxic conditions and subsequently exposed to hypoxia. Astrocyte-derived EVs released into the supernatant were collected separately from both conditions. Label-free mass spectrometry-based proteomics was then performed to assess the effects of hypoxia on the EV protein cargo. A meta-analysis comparing the results with previously published EV proteomic datasets was also conducted.ResultsThis study revealed a differential expression of 83 upregulated proteins under hypoxic conditions and 61 downregulated proteins under normoxic conditions, highlighting the protective protein signatures elicited by astrocytes. The dataset has been deposited in the ProteomeXchange Consortium with the identified PXD050160.ConclusionThe present study makes a novel contribution by employing proteomic techniques to characterize the protein cargo of EVs isolated from primary rat astrocytes. This approach enables a more refined analysis of astrocyte-specific intercellular signaling under hypoxic conditions and provides valuable insights into the roles of astrocytes in maintaining brain homeostasis and contributing to pathological processes.
Keywords: neuroprotection